Odwołanie darowizny w polskim kodeksie zobowiązań z 1933 r. - Baszak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article provides an analysis of the provisions of the Polish Code of Obligations of 1933 concerning cancellation of donation. The author discusses the provisions of Articles 364–369 of the Code, taking into account the impact of the various donation cancellation provisions included in regional codes and in other civil codes, i.e. the German Civil Code of 1896; Austrian Civil Code of 1811; Napoleonic Code of 1804; volume X, part 1 of the Russian Svod Zakonov Rossiyskoy Imperii of 1832; Swiss obligation law of 1911 and the draft Russian law of obligations of 1913. He also compares the final versions of the articles with their versions from the draft law of obligations by Dr Ernest Till and Prof Roman Longchamps de Berier, who were members of the Codification Commission. In addition, the author cites selected judgements of the Supreme Court dealing with the matterThe article provides an analysis of the provisions of the Polish Code of Obligations of 1933 concerning cancellation of donation. The author discusses the provisions of Articles 364–369 of the Code, taking into account the impact of the various donation cancellation provisions included in regional codes and in other civil codes, i.e. the German Civil Code of 1896; Austrian Civil Code of 1811; Napoleonic Code of 1804; volume X, part 1 of the Russian Svod Zakonov Rossiyskoy Imperii of 1832; Swiss obligation law of 1911 and the draft Russian law of obligations of 1913. He also compares the final versions of the articles with their versions from the draft law of obligations by Dr Ernest Till and Prof Roman Longchamps de Berier, who were members of the Codification Commission. In addition, the author cites selected judgements of the Supreme Court dealing with the matter
Keywords: odwołanie darowizny; kodeks zobowiązań; darowizna